Anthropometric Characteristics of Vegetarian and Non- Vegetarian Adults in a Selected Local Government Area In Osun State, Nigeria - Olariike Oyindasola Kayode; Akin Oyebade; Adeola Oluwaseun Oshineye; Abayomi Tolu Olarinmoye; Ayodeji Akinyemi Akinpelu (Adventist University of Africa, 2024)
Background: Vegetarian diets have grown in popularity partly because they have been linked to numerous health benefits. They are typically high in fiber and antioxidants and low in cholesterol, potentially lowering the risk of chronic diseases. On the other hand, diets established on meat and its products play a significant role in increasing the incidence of non-communicable diseases owing to their increased calorie density and extra saturated fat. Methods: A cross-sectional study was conducted among 121 adults recruited purposively from two Seventh-day Adventist churches in the Ede South Local Government area of Osun State. Results: Most respondents (73.6 %) were non-vegetarian and 26.4% were vegetarian (65.6% semi-vegetarian, 25% lacto-ovo, and 9.4% vegans). Among the non-vegetarians, 4.0% were underweight, 42.0% were of normal weight, 44.0% were overweight, and 10.1 % were obese. Among Vegetarians, 56.3% and 43.7% were of normal weight and overweight, respectively. Conclusion: The prevalence of obesity among non-vegetarians was high, indicating the need for nutritional education intervention on the health benefits of a vegetarian diet.